"The Noblest Roman of them all?" Professional versus Popular Views of America's Country Doctors. (17th November 2020) - Borst, Charlotte G
Abstract: This essay studies the images, perceptions, and values of the professional medical journals, as well as popular sources such as magazine and films, to show that the country doctor was a contested figure in the late nineteenth and early twentieth centuries. The country doctor's image embodied competing ideals of a racialized professional and masculine identity that included both place as well as visions of science. Medical professionals pressed an image in their journals and professional advice books that mapped a celebration of science and its predictive value onto urban places that were enshrined in hospitals and laboratory facilities. The public, while embracing this image, also embraced a second one shown in popular media that glorified the self-sacrificing rural solo practitioner. This practitioner's wisdom came from long contact with patients, he was dedicated to seeing patients in their homes, and his identity was based in the larger needs of the entire community.